The Effect of Leadership Style, Motivation and Work Discipline on Employee Performance - Hamdi, Hamdi; Aqmarina, Nur; Kadir, Abdul; Naimah, Naimah (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this study was to describe, analyze and find out the most dominant influence of competence, motivation, work discipline on the performance of the employees of the "Handayati" Public Hospital in Tapin District. To analyze the problem, 30 respondents were used through the nonprobability sampling method. Data collection techniques using survey methods with closed questionnaire tools. Data analysis was performed using validity, reliability testing, descriptive analysis and multiple linear regression analysis. Data processing uses SPSS Version 22.00. The results showed that partially human resource competency (X1) did not significantly influence the performance of 0.360 <0.05, work motivation (X2) partially had a significant effect on the performance of 0.002> 0.05 and work discipline (X3) partially had an effect significant to the performance of 0,000> 0.05. Simultaneously independent variables (HR competence, work motivation and work discipline) significantly influence the performance of R2 (coefficient of determination) of 0.877 or 87.7% or the remaining 22.3% influenced by other factors beyond the three independent variables. Work discipline is the most dominant variable that influences the performance with a beta value of 0.806 compared to work motivation variable 0.321 and HR competency variable -0.096.